Brown rice and retrograded brown rice alleviate inflammatory response in dextran sulfate sodium (DSS)-induced colitis mice. Issue 12 (17th November 2017) - Praengam, Kemika; Sahasakul, Yuraporn; Kupradinun, Piengchai; Sakarin, Siriwan; Sanitchua, Wanwisa; Rungsipipat, Anudep; Rattanapinyopituk, Kasem; Angkasekwinai, Pornpimon; Changsri, Khaimuk; Mhuantong, Wuttichai; Tangphatsornruang, Sithichoke; Tuntipopipat, Siriporn
Abstract : We investigate the impact of brown rice and retrograded brown rice consumption on colonic health in dextran sulfate sodium induced colitis mice. Abstract : The present study was aimed to investigate the impacts of brown rice (BR) and retrograded brown rice (R-BR) consumption on colonic health and gut microbiota in dextran sulfate sodium (DSS) induced colitis mice. Thirty two female C57Bl/6Mlac mice were fed with modified AIN 93G diets by replacing cornstarch in the original composition with white rice (WR), BR and R-BR powder. The mice were divided into 4 groups and fed with the following experimental diets for 4 weeks: (1) negative control (WR: diet with WR), (2) positive control (DSS_WR: DSS and diet with WR), (3) DSS_BR: DSS and diet with BR, and (4) DSS_R-BR: DSS and diet with R-BR. BR and R-BR had a greater content of fat, dietary fiber, GABA, γ-oryzanol, γ-tocotrienol, ferulic acid and p -coumaric acid than WR ( p < 0.05). No significant difference in the level of these bioactive compounds was noted between BR and R-BR. Nevertheless, R-BR had a 1.8 fold resistant starch (RS) content of BR ( p < 0.05). The DSS_BR and DSS_R-BR groups showed a lower ratio of colonic weight to length, and a lower content of iNOS, COX-2, MPO, IL-6 and INF-γ in colonic homogenates than the DSS_WR group. However, the DSS treated mice fed with the R-BR diet had significantly milder histopathological inflammatory injury and lower colonic iNOS expression than the DSS_BR and DSS_WR groups. The percentage of mesenteric regulatory T cells significantly increased in the DSS_R-BR group compared to that in the DSS_WR group. The DSS treated mice fed with the R-BR diet showed a significant increase in cecal bacterial diversity and abundance of genera Prevotella, Ruminococcus, Dorea, Coprococcus and Dehalobacterium but a significant decrease in pathogenic bacteria including Bacteroides and Enterococcus compared to the DSS_WR group. Thus, the present data indicate that BR and R-BR ameliorate colonic inflammation in experimental colitis induced by DSS in mice by suppressing inflammatory mediators and modulating regulatory T cell responses as well as bacterial diversity in the cecum.